Implantación de un sistema de gestión de seguridad y salud ocupacional en comercial molinera san luis, lambayeque - Jiménez Cervantes, Noé (2016)
The objective of the research was to establish a system of safety management and occupational health in Commercial Molinera San Luis. To achieve this document fieldwork to observe the facilities and the production process, in order to take notes to identify risks powers in the process safety management and greet taken by the company was made. Part desk job was to request supporting documentation available to the company, and then compare it with the rules and regulations governing safety and health in the country. For the preparation of diagnosis used two techniques such as questionnaire survey type and IPER risk matrix of the task. The result showed that the most common risks were the mechanical, chemical and biological. In estimating risk it was determined that 65% were at significant risk, moderate risk 20% and 15% intolerant risks. Other problems found were the lack of departmental objectives safety and health, breach of legal requirements, lack of control of the management system documentation, lack of a training plan based on a needs assessment. The conclusion was that implementation of a management system for occupational safety and health helped improve compliance with safety and health at work.